Correlation Analysis of Serum Lipopolysaccharide, Nuclear Factor Erythroid 2-Related Factor 2 and Haem Oxygenase 1 Levels and Cognitive Impairment in Patients with Obstructive Sleep Apnoea - Feng G; Zhuge P; Zou Y; Zhang Z; Guo J; Ma J (Dove Medical Press, 2024)
Guofei Feng, Pan Zhuge, Yaping Zou, Zhifeng Zhang, Jiandong Guo, Junxiang Ma Department of ENT, Jinhua Central Hospital, Jinhua, Zhejiang, 321000, People's Republic of ChinaCorrespondence: Guofei Feng, Department of ENT, Jinhua Central Hospital, No. 365, East Renmin Road, Jinhua, Zhejiang, 321000, People's Republic of China, Tel/Fax +86 579 82552620, Email guofeifeng1781f@163.comObjective: To investigate the correlation between the levels of serum lipopolysaccharide (LPS), nuclear factor erythroid 2-related factor 2 (Nrf2), haem oxygenase 1 (HO-1) and cognitive impairment in patients with obstructive sleep apnoea (OSA).Methods: Serum LPS, Nrf2, HO-1 levels and cognitive impairment were measured using the Montreal Cognitive Assessment (MoCA) score in 56 patients in the "severe" group, 67 patients in the "mild-to-moderate" group and 100 healthy people in the "control" group. The differences in general conditions and serological indexes between the three groups were compared, the correlation between the MoCA scores and the serological indexes was explored and the independent predictors of the MoCA scores were analysed.Results: Serum LPS, Nrf2 and HO-1 levels were higher in the severe group than in the mild-to-moderate group and the control group (p < 0.05). A total of 71 patients with OSA had combined cognitive impairment, accounting for 57.7%, and the MoCA scores were lower in the severe group than in the mild-to-moderate group and the control group (p = 0.018). Serum LPS, Nrf2 and HO-1 levels were significantly higher in the severe group and mild-to-moderate group than in the control group (p < 0.05) and were negatively correlated with the MoCA scores. Lipopolysaccharide (p < 0.001) and HO-1 (p = 0.002) could be considered independent predictors of the MoCA score.Conclusion: Serum LPS and HO-1 levels are closely related to cognitive impairment in patients with OSA and have potential clinical value in the diagnosis.Keywords: obstructive sleep apnoea, cognitive impairment, lipopolysaccharide, nuclear factor erythroid 2-related factor 2, haem oxygenase 1